„Gazeta Wyborcza” i „Rzeczpospolita” wobec wyroku Trybunału Konstytucyjnego z dnia 11 maja 2007 r. w sprawie ustawy lustracyjnej (analiza porównawcza) - Jęczmionka, Paulina (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
The article deals with a problem of vetting in the press discourse taken “Gazeta Wyborcza” and “Rzeczpospolita” as an example. There is an attempt to present oppositional attitudes of both titles against each other. All the articles about a vetting problem a week before and after May 11, 2007 were analyzed. Some questions had also been asked. Was the sentence similarly commented by both newspapers and Why was it commented in a particular way? After the analysis, the hypothesis was confirmed. That is, the comments on the sentence were opposite and unbalanced. It was because of different newspapers’ programme lines. It was ascertained that “Gazeta Wyborcza” was against the vetting whereas “Rzeczpospolita” supported it.